Bagasse minority pathway expression: Real time study of GH2 β-mannosidases from bacteroidetes. - Tatiane Fernanda Leonel; Elisângela Soares Gomes Pepe; Tereza Cristina Luque Castellane; Juliana da Silva Vantini; Michelli Inácio Gonçalves Funnicelli; Eliana Gertrudes de Macedo Lemos (PLoS ONE, 2021)
After being isolated from a sugarcane pile, the bacterium Chitinophaga sp. CB10 demonstrated to be a rich source of carbohydrases, with 350 predicted CAZyme domains. CB10 was able to grow on carbohydrates of different structural complexities: glucose, carboxymethylcellulose, corn starch, galactomannan, Aloe vera gum and sugarcane bagasse. The sugarcane bagasse is a rich source of complex polymers, and the diversity of metabolites released by its enzymatic hydrolysis has an important role for green chemistry, including minority pathways such as the degradation of mannan conjugates. In this sense, CB10 demonstrated considerable levels of gene expression for mannanases, and was stable for a period of 96-144 hours in the presence of sugarcane bagasse as sole carbon source. The bacterium showed respectively 4.8x and 5.6x expression levels for two genes predicted for GH2 β-mannosidase: one located within a gene cluster identified as "polysaccharide utilization loci" (PUL), and another a classic β-mannosidase. These enzymes shared less than 45% of identity with enzymes characterized from the genus Chitinophaga belonging to the phylum Bacteroidetes. The degree of novelty-as demonstrated by the low identity with previously characterized enzymes; the remarkable capability to grow in different substrates; mannanase activity, evidenced by the release of residual oligosaccharides in the cultivation with galactomannan (HPLC-RID, 12.3 mMol); associated to the ability of mannanases expression in a low concentration of inductor conditions (sugarcane bagasse, 0.2%) indicate the high potential for the application of CB10 as a source of enzymes in the production of oligosaccharides from biomass. This capacity might prove to be very valuable for the biorefinery process of pre-biotic precursors and other functional oligosaccharides focused on the food and pharmaceutical industries.